Genetics polymorphism of poplars from Moscow region based on high-throughput sequencing of ITS - E. V. Borkhert; G. S. Krasnov; N. L. Bolsheva; Р. Kezimana; O. Yu. Yurkevich; O. V. Muravenko; A. V. Kudryavtseva; N. V. Melnikova (Вавиловский журнал генетики и селекции)
Poplars are widely used in landscaping of Moscow due to the ability to effectively purify the air from harmful impurities and to release a large amount of oxygen. The genus Populus is characterized by a high level of intraspecies polymorphism, as well as the presence of natural interspecies hybrids. The aim of our work was to evaluate the genetic diversity of poplars, which are growing on the territory of Moscow city by high-throughput sequencing of internal transcribed spacers of 45S rRNA genes (ITS sequences). Sequencing of ITS of 40 poplar plants was performed on Illumina platform (MiSeq) and about 3 000 reads were obtained for each sample in average. Bioinformatics analysis was performed using CLC Genomics Workbench tool. The involved set of poplars had a high level of genetic diversity – the number of single nucleotide polymorphisms (SNPs) detected in each genotype relative to the reference ITS1 and ITS2 sequences of P. trichocarpa varying from 4 to 44. We showed that even trees which had been planted on the same territory and, probably, at the same time had significant genetic differences. It can be speculated that highly polymorphic plant material was used for planting poplars in Moscow. For some sites with SNPs, several variants of nucleotides were found in the same individual and the ratio of SNPs was different. We assume that close to 50/50 ratio is observed in interspecific hybrids due to genetic differences in the ITS sequences between maternal and paternal genotypes. For SNPs with a predominance of one of the variants, the presence of paralogues among numerous genomic copies of ITS sequences is more likely. The results of our work can provide a framework for molecular genetic markers application with the purpose of Populus species and interspecific hybrids identification, determination the origin of a number of natural hybrids, and monitoring the diversity of genus Populus in the Moscow city.